PELATIHAN SOFTSKILL MARKETING USAHA AGRIBISNIS PADA SISWA SMK SWAGAYA 2 PURWOKERTO - Sulistyani Budiningsih; Pujiati Utami (Universitas Muhammadiyah Purwokerto, 2013)
This training partner is SMK Swagaya 2 Purwokerto with the consideration of the early result evaluation which conducted when Workshop Curriculum of Agribusiness Department of Agricultural Faculty was held. It found that majority (> 80 %) schoolgirl student was having less interest and enthusiasm to agriculture which include Agribusiness in it. This activity aims to (1) give the information and knowledge to schoolgirl student of SMK about agriculture specially agribusiness, (2) increase their interest and enthusiasm to Agribusiness and (3) give the training about Agribusiness Marketing’s Soft skill. The result showed that knowledge and understanding which deal with agricultural business soft skill was getting higher to whom that attended the activity. Key words: knowledge, soft skill and entrepreneurrship